Advantageous Functional Integration of Adsorption‐Intercalation‐Conversion Hybrid Mechanisms in 3D Flexible Nb2O5@Hard Carbon@MoS2@Soft Carbon Fiber Paper Anodes for Ultrafast and Super‐Stable Sodium Storage. (20th January 2020) - Deng, Qinglin; Chen, Feng; Liu, Si; Bayaguud, Aruuhan; Feng, Yuezhan; Zhang, Zhibo; Fu, Yanpeng; Yu, Yan; Zhu, Changbao
Abstract: Using synergetic effects of various sodium storage modes and materials to construct high power, high energy, and long cycling flexible sodium anode materials is significant and still challenging. Here, by advantageous functional integration of adsorption‐intercalation‐conversion sodium storage mechanisms, a 3D flexible fiber paper anode with the composition of Nb2 O5 @hard carbon@MoS2 @soft carbon is designed and prepared. Based on the synergetic effects, it exhibits higher specific capacity than pure Nb2 O5, with more excellent rate performance (245, 201, 155, 133, and 97 mAh g −1 at the current density of 0.2, 1, 5, 10, and 20 A g −1, respectively) than pure MoS2 as well as admirable long‐term cycling characteristics (≈82% capacity retention after 20 000 cycles at 5 A g −1 ). Relevant kinetics mechanisms are expounded in detail. This work can be helpful for preparing other types of hybrid and flexible electrodes for energy storage systems. Abstract : By advantageous functional integration of adsorption‐intercalation‐conversion mechanisms, a 3D flexible Nb2 O5 @hard carbon@MoS2 @soft carbon fiber paper electrode is prepared. This hybrid anode can release the sodium storage advantages of all materials with the aid of synergetic effects. It displays excellent rate performance and long‐term cycling for over 20 000 cycles.